1997
DOI: 10.1177/014920639702300503
|View full text |Cite
|
Sign up to set email alerts
|

When Two Factors Don’t Reflect Two Constructs: How Item Characteristics Can Produce Artifactual Factors

Abstract: Factor analyses of scales that contain items written in opposite directions sometimes show two factors, each of which contains items written in only one direction. Such item direction factors have been found in scales of affect and personality that have been used in organizational research. We discuss how patterns of subject responses to items that vary in direction and extremity can produce an arttfactual two factor structure in the absence of multiple constructs. Response patterns are demonstrated in Study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(89 citation statements)
references
References 30 publications
3
79
0
7
Order By: Relevance
“…This type of inappropriate response to negatively worded items can be interpreted as a method artifact and may be responsible for the appearance of separate factors associated with positively and negatively worded items in previous exploratory factor analyses (Spector et al, 1997). Marsh (1986) showed that the size of the negative item bias varied substantially with age among several student samples.…”
Section: The Negative Item Biasmentioning
confidence: 93%
See 1 more Smart Citation
“…This type of inappropriate response to negatively worded items can be interpreted as a method artifact and may be responsible for the appearance of separate factors associated with positively and negatively worded items in previous exploratory factor analyses (Spector et al, 1997). Marsh (1986) showed that the size of the negative item bias varied substantially with age among several student samples.…”
Section: The Negative Item Biasmentioning
confidence: 93%
“…Although psychometric studies have generally supported the unidimensionality of the RSES (Carmines & Zeller, 1979;Corwyn, 2000;Dunbar, Ford, Hunt, & Der, 2000;Fleming & Courtney, 1984;Marsh, 1996;O'Brien, 1985), when multiple factors have been reported, the tendency is for the positively and negatively coded items of the RSES to form two separate factors. A tendency for positive and negative items to group into two factors does not necessarily reflect a substantively important distinction between positive and negative self-esteem, however (Greenberger, Chen, Dmitrieva, & Farruggia, 2003;Spector, Van Katwyk, Brannick, & Chen, 1997). The differential behavior of positively and negatively worded items may mirror a substantively irrelevant method effect (Marsh, 1996).…”
Section: External Equivalence Of Global Self-esteemmentioning
confidence: 95%
“…7 . Essa característica, não obstante, pode não ser recomendável quando se tem por objetivo medir outros construtos, como traços de personalidade e indicadores de afetos e bem-estar subjetivo, podendo criar um fator espúrio 8,9 .…”
unclassified
“…Porém, como Hankins 16 indica, embora alguns estudos definam este instrumento como multifatorial, as evidências correspondentes podem ser proporcionadas por um fenômeno conhecido como efeito do método. Concretamente, o emprego de itens positivos e negativos em uma medida, embora possa minimizar o erro de aquiescência, produz potencialmente ao menos um fator adicional ou torna a estrutura fatorial mais complexa do que seria de fato 9 . Esse problema é o foco principal do presente trabalho, cujo objetivo é avaliar a estrutura fatorial do QSG-12, tendo em conta o possível efeito da redação dos itens.…”
unclassified
“…This raises the issue of "common method variance" (Podsakoff, 1986). Spector et al (1997) have argued that the most effective way to overcome common method variance, other than methodological weaknesses is to test ideas with different methods. For example, an experimental verification could be provided of the relationships found in a survey method.…”
Section: Resultsmentioning
confidence: 99%